Development assistance, rudimentary financial markets and relatively rapid goods market adjustments - Singh, Thomas B. (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Suggests that the institutional and structural features of developing countries imply that goods market adjustment may actually precede and be faster than asset market adjustment to real of financial shocks. Further argues that such adjustment may be the natural consequence of two key features of developing countries viz. that financial markets are underdeveloped and that goods markets are dominated by the production of primary goods that usually entail high inventory costs.